2003
DOI: 10.1176/appi.ajp.160.4.773
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette Smoking, Suicidal Behavior, and Serotonin Function in Major Psychiatric Disorders

Abstract: The association between cigarette smoking and the presence and severity of suicidal behavior across major psychiatric disorders may be related to lower brain serotonin function in smokers with depression. Further investigation is required to replicate these findings, to measure serotonin function in patients with disorders other than depression, and to test potential therapeutic effects of serotonin-enhancing treatments on both smoking behavior and suicide risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
182
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 245 publications
(194 citation statements)
references
References 54 publications
9
182
0
Order By: Relevance
“…28,29 In human studies Malone et al have reported a correlation between cigarette smoking and impaired serotonin function in depressed patients by measuring cerebrospinal fluid 5-hydroxyindoleacetic acid level and investigating prolactin response to fenfluramine. 7 Reduced serotonergic function in the brain is also suggested by studying the post-mortem brains of depressed suicide victims; they have lower brainstem levels of 5HT and 5HIAA, and fewer 5HTT binding sites in the prefrontal cortex. 12 In vivo imaging and post-mortem brain studies conducted in depressed patients suggested that reduced 5HTT binding is widespread in the brain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…28,29 In human studies Malone et al have reported a correlation between cigarette smoking and impaired serotonin function in depressed patients by measuring cerebrospinal fluid 5-hydroxyindoleacetic acid level and investigating prolactin response to fenfluramine. 7 Reduced serotonergic function in the brain is also suggested by studying the post-mortem brains of depressed suicide victims; they have lower brainstem levels of 5HT and 5HIAA, and fewer 5HTT binding sites in the prefrontal cortex. 12 In vivo imaging and post-mortem brain studies conducted in depressed patients suggested that reduced 5HTT binding is widespread in the brain.…”
Section: Discussionmentioning
confidence: 99%
“…Male Wistar rats were implanted with a minipump s.c., which delivered nicotine at a rate of 6 mg/kg per day for 12 days (days [1][2][3][4][5][6][7][8][9][10][11][12]. Rats given chronic nicotine were killed on day 13, or 2 days after the removal of minipump (withdrawal day 2).…”
Section: Methodsmentioning
confidence: 99%
“…HVA and MHPG CSF concentrations were inversely correlated with the number of cigarettes smoked/day, while we did not find any significant Association between MAOA, dopamine function and BMI F Ducci et al effect of smoking on 5-HIAA levels (see Table 2). Since the effect of smoking on 5-HIAA has been reported in depressed patients, 43 we examined the effect of smoking versus nonsmoking on 5-HIAA levels. Smokers had lower 5-HIAA (67.1, s.e.…”
Section: Mhpg Csf Mhpg Levels Did Not Differ Between the Two Genotypmentioning
confidence: 99%
“…Prenatal smoking exposure may have a long-term influence on offspring serotonin metabolism. Chronic nicotine exposure reduces serotonin metabolism in animals [16], smokers have reduced serotonin levels in the cerebrospinal fluid [17], and reduced serotonin levels is associated with increased risks of suicidal acts [18]. Using a large population-based data set, we studied the association between maternal smoking during pregnancy and risk of completed suicide and suicidal acts in young offspring after taking family history of psychiatric diseases into account.…”
Section: Introductionmentioning
confidence: 99%